Benjamin Rush and his role in the American Revolutionary War: (1773-1783) - Khudair, Ayat; Abdullah, Nagham (Al-Adab Journal, 2024)
The American War of Independence shed light on many of the leaders of the Generation of the Founding Fathers of the New Young Republic, and the character of Benjamin Rush is the most prominent of those names, starting from the early stages of his life in which he paved the way towards choosing the medical profession, passing through the signs of the emergence of the National Issue and the escalation of the dispute between the colonists and their mother country, His advocacy of the revolution, his immersion in political work in support of it with determination and persistence, his signing of the Declaration of Independence, support for the strong central government, his keenness to improve the moral and behavioral aspect of individuals as part of the process of building the state properly with all its institutions, and his involvement in writing, authoring and publishing in various fields and branches of science and knowledge.